2012
DOI: 10.1097/bot.0b013e3182143de0
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Pinning in Supracondylar Fracture of the Humerus in Children

Abstract: Lateral pinning is preferable to cross pinning for fixation of pediatric supracondylar humerus fractures as a result of decreased risk of ulnar nerve injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 29 publications
4
75
0
7
Order By: Relevance
“…The patient's age at the time of fracture was also equally similar: 5.9 years (2,4,(26)(27)(28)(29) . The development of compartment syndrome is the most feared complication of this type of injury.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The patient's age at the time of fracture was also equally similar: 5.9 years (2,4,(26)(27)(28)(29) . The development of compartment syndrome is the most feared complication of this type of injury.…”
Section: Discussionmentioning
confidence: 83%
“…Cubitus varus is considered the most common late complication in this type of fracture, presenting an incidence of 20% in our series. Other authors who used closed reduction and percutaneous fixation reported lower rates of around 10% (1,(3)(4)(5)(6)(14)(15)(16)(17)(18)22,25,(27)(28)(29) . The initial deviation and ligamentotaxis are the main factors mechanically influencing the final result of the fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few meta-analyses or systematic reviews compared the postoperative functional outcomes. Woratanarat et al [57] performed a meta-analysis to compare the criteria of Flynn et al for the two pin fixation techniques, but there were insufficient RCTs to pool data until September 2007. The current meta-analysis included three studies which reported the criteria of Flynn et al Further, no major differences were found concerning the outcomes between the lateral entry pin and crossed entry pin in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although several meta-analyses or systematic reviews of lateral entry versus crossed medial and lateral entry pinning for supracondylar fractures of the humerus have been reported [3,5,29,38,52,57], the conclusions drawn are based largely on results from nonrandomized controlled trials (nRCTs), which increases the likelihood that bias has affected those analyses. Randomized controlled trials (RCTs) are considered to be the most reliable form of scientific evidence in the hierarchy of evidence because they reduce spurious inferences of causality and bias.…”
Section: Introductionmentioning
confidence: 99%